Psychosocial Factors and Tobacco Use Among Commercial Truck Drivers. Issue 6 (June 2020) - Kagabo, Robert; Okuyemi, Kola; Eden, Emilee; Kapellusch, Jay; Murtaugh, Maureen A.; Hegmann, Kurt T.; Thiese, Matthew S.
Abstract : Objectives: To explore the relationships between tobacco, social support, job satisfaction, and depression among truck drivers. Methods: Cross-sectional data were collected from 797 truck drivers in six US states. Data collected included self-reported medical history and biological samples. Modified Zung depression scale and Work Apgar scores were used to measure depression and social support. Adjusted logistic regression models were used to calculate odds ratios (OR). Results: 24.0% of tobacco users were in the least depressed category and 18.2% were most depressed. 22.8% of the tobacco users had the most social support compared with 27.9% of the non-users. Drivers in the two most depressed categories were significantly less likely to use tobacco (OR = 0.62, 95% confidence interval [CI] = 0.39–0.96, and OR = 0.64, 95% CI = 0.41–0.99). Conclusions: Drivers with low social support or low levels of depression are more likely to be tobacco users.